"Bettwäsche ist rar; es lässt sich aber auch auf einem Haufen Lumpen schlafen."
internationale Politik (allgemein);internationale Beziehungen;Entwicklungszusammenarbeit;Hilfswerk soziale Fragen;Leben in der Gesellschaft (allgemein);soziales Problem;Armut